Pemanfaatan Aplikasi Audacity pada Pembelajaran Istima' Kelas XI MAS Madinatun Najjah - Amrina Amrina; Adam Mudinillah; syarifah zaharani (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2021)
Istima 'is a very important way of mastering Arabic, by listening to a voice we will have another point of view in understanding and deepening Arabic. Listening techniques are also used at the lecture level, in this case there is no possibility for high school and elementary school levels to use the Istima technique in their learning process in order to improve understanding and proficiency in listening. Not only Istima 'In Arabic lessons there are various techniques or methods that can be used to broadly understand Arabic. There are many applications that can be used in this case, in this learning there are various divisions of skills to master Arabic perfectly, so that students not only master certain fields but are also proficient in writing, speaking, using Arabic. Among them are Maharah Kalam, Maharah Istima, Maharah Qiroah and Maharah Kitabah. In this scientific paper, the author is more focused on Maharah Istima' (hearing), this technique is very foreign to those who are not familiar with what Maharah is in language learning. this Arabic. In this modern era, there are many media that can be used for Maharah Istima', including Mixpad, Audacity, and others. In this Scientific Work, the author uses the Audacity Application as a Media in Maharah Istima' lessons, Mixpad applications can also be used in this Maharah lesson, by In other words, it's not just these 2 applications that readers can use in learning, but there are still many out there available various digital technologies and applications that are very useful for mastering and understanding Arabic lessons. This application can be used on mobile phones and laptops. This application can also capture sound from a headset connected to a laptop.